The decline of the South African economy - Jones, Stuart, 1933-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2002)
South Africa's leading economists adopt within this volume a sectoral approach in their analysis of the drastic changes that have occurred within the South African economy since 1970. The book illustrates how, despite its sophisticated infrastructure, the South African economy has shared in the economic decline - resulting from misguided economic policies - that has been the experience of Sub-Saharan Africa.
1. Introduction / Stuart Jones -- 2. Economic survey, 1970-2000 / Gavin Maasdorp -- 3. Macroeconomic policy, 1970-2000 / P.D.F. Strydom -- 4. Agriculture, 1970-2000 / Nick Vink and Stefan Schirmer -- 5. The mining sector, 1970-2000. I, The years of turbulence, 1970-2000 / Stuart Jones. II, Transformation in the 1990s / Stuart Jones and Roger Baxter -- 6. The manufacturing industry, 1970-2000 / Trevor Bell and Nkosi Madula -- 7. The freight transport sector, 1970-2000 / Trevor Jones -- 8. The financial sector, 1970-2000 / Stuart Jones -- 9. External trade, 1970-2000 / Stuart Jones -- 10. Balance of payments, 1970-1999 / Philip Mohr -- 11. The situation in 2000 / Stuart Jones.
Includes bibliographical references and index.
Keywords: South Africa -- Economic conditions -- 1961-1991.; Electronic books